Cloning, purification, and characterization of xylose isomerase from Thermotoga naphthophila RKU‐10. (26th April 2016) - Fatima, Bilqees; Aftab, Muhammad Nauman; Haq, Ikram‐ul
Abstract : A 1.3 kb xyl‐A gene encoding xylose isomerase from a hyperthermophilic eubacterium Thermotoga naphthophila RKU‐10 (TnapXI) was cloned and over‐expressed in Escherichia coli to produce the enzyme in mesophilic conditions that work at high temperature. The enzyme was concentrated by lyophilization and purified by heat treatment, fractional precipitation, and UNOsphere Q anion‐exchange column chromatography to homogeneity level. The apparent molecular mass was estimated by SDS–PAGE to be 49.5 kDa. The active enzyme showed a clear zone on Native‐PAGE when stained with 2, 3, 5‐triphenyltetrazolium chloride. The optimum temperature and pH for D‐glucose to D‐fructose isomerization were 98 °C and 7.0, respectively. Xylose isomerase retains 85% of its activity at 50 °C ( t 1/2 1732 min) for 4 h and 32.5% at 90 °C ( t 1/2 58 min) for 2 h. It retains 90–95% of its activity at pH 6.5–7.5 for 30 min. The enzyme was highly activated (350%) with the addition of 0.5 mM Co 2+ and to a lesser extent about 180 and 80% with the addition of 5 and 10 mM Mn 2+ and Mg 2+, respectively but it was inhibited (54–90%) in the presence of 0.5–10 mM Ca 2+ with respect to apo‐enzyme. D‐glucose isomerization product was also analyzed by Thin Layer Chromatography ( R f 0.65). The enzyme was very stable at neutral pH and sufficiently high temperature and required only a trace amount of Co 2+ for its optimal activity and stability. Overall, 52.2% conversion of D‐glucose to D‐fructose was achieved by TnapXI. Thus, it has a great potential for industrial applications.